Hippocampal mitochondrial Ca++ in experimentally induced Alzheimer's disease, link to calpains and impact of vitamin D3 supplementation - Zienab Alrefaie; Jana Bashraheel; Hossam A. Hammad; Soad S. Ali; Ahlam Alahmadi (Elsevier, 2023)
Objective: Vitamin D impact on hippocampal mitochondrial Ca++ and calpains was not previously investigated in Alzheimer's disease (AD). The current work aimed to assess the alteration in hippocampal mitochondrial Ca++, ATP & ADP and hippocampal calpains' level in (AlCl3)-induced AD model, and the effect of 2 regimens of vitamin D supplementation on these alterations. Methods: Forty male Wistar rats were randomized into 4 groups; control, AD (AlCl3100 mg/kg, p.o. daily for 42 days), AD and vitamin D co-treated group (AlCl3 as in AD group with vitamin D3 400 IU/kg/day, p.o. for 42 days) and AD, followed by vitamin D3 group (AlCl3 was given as in AD group for 42 days, then vitamin D3 for two weeks). AD was assessed by hippocampal levels of Aβ42, p-tau and spatial memory assessment in Morris water maze. Hippocampal mitochondrial Ca++, ATP and ADP levels besides to calpain-1 & 2 and cytochrome C were assessed in addition to CA1 histological examination. Results: AD animals showed impaired mitochondrial function as denoted by high Ca++ and decreased ATP and ADP and elevated calpain-1 & 2 and cytochrome C. Hippocampal CA1 region showed increased degenerated neurons and reduced thickness of its pyramidal layer. Vitamin D administration minimized the hippocampal mitochondrial impairement induced by AD and mitigated histological alterations even when supplemented post AD establishment. Conclusion: Vitamin D administration to AD rats breaks the deleterious loop in the hippocampus that involves increased Ca++, calpain activation, mitochondrial failure, neuronal degeneration and AD disease progression.